ASSESSMENT OF «BIFIFORM» EFFICACY IN PATIENTS WITH JUVENILE ARTHRITIS TREATED WITH ANTIBIOTICS - S.I. Valieva; E.I. Alexeeva; T.M. Bzarova; K.B. Isaeva; A.O. Lisitsin; A.M. Bzarova; R.V. Denisova ("Paediatrician" Publishers LLC, 2008)
Activity of probiotic medication «Bifiform» in children with juvenile arthritis treated with antibiotics is described in this article. Prophylactic application of prebiotic before beginning of antibacterial treatment in base group of patients allows avoiding antibiotic associated diarrhea. «Bifiform» stops diarrhea and other dyspeptic events in patients treated with antibiotics with manifestations of dyspepsia on average in 3 days of therapy. It's recommended to use «Bifiform» in patients with juvenile arthritis treated with wide spectrum antibiotics to prevent dyspepsia. Key words: children, juvenile arthritis, antibacterial treatment, probiotics.